EDP case study : how to initiate and organize digital transformation - Ydstebø, André (2019)
With the rise of a digital economy, Weill and Woerner (2015b) found that Digital disruption threatens 46% of revenues within the next 5 years for firms with a revenue greater than 7B $, motivating enterprises across industries to renew their business models and the organizations´ DNA to thrive in the future. In my thesis, I have chosen to develop a teaching case which intends to illustrate how a traditional company can initiate and organize Digital Transformation as a starting point to successfully transform itself to succeed in the digital era. I have selected the company EDP Energias de Portugal for this matter. The case presents how Energias de Portugal initiated Digital Transformation, enabling the students to analyze and find insights from their approach, the challenges that occurred, and the concerns behind the major decisions required. From interviewing key-persons behind EDP´s Digital Transformation efforts, it was emphasized that people-related challenges were the main hindrance, and that communication and involvement played a vital role to drive cultural changes, acquire digital talent, and gain support for the initiates.